MENINGKATKAN LITERASI PAJAK UMKM DI KAMPUNG TUA TELUK MATA IKAN, NONGSA - BATAM - Onoyi, Nona Jane; Kurniawati, Ely; Windayati, Diana Titik (Jurnal Pengabdian Ibnu Sina, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the national economy, yet tax literacy among MSMEs remains low. This community service activity aims to improve MSME tax understanding through communicative and hands-on education in Kampung Tua Teluk Mata Ikan, Batam. Implementation methods included observation, preparation of materials based on the latest regulations (PP 55/2022 and PMK 164/2023), interactive outreach, tax reporting simulations, and evaluation through pre- and post-tests. The activity results showed a significant increase in participants' understanding of tax obligations. A down-to-earth, non-intimidating approach proved effective in creating a comfortable learning environment. The involvement of lecturers and students as facilitators also strengthened emotional bonds with participants. Challenges such as limited revenue recording were addressed by providing simple tools. This program not only impacted tax literacy but also encouraged changes in attitudes toward voluntary tax compliance. These findings underscore the importance of synergy between universities and the community in building an inclusive and sustainable tax culture.